2018
DOI: 10.1002/brb3.1081
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported and performance‐based measures of walking in mild–moderate Parkinson's disease

Abstract: BackgroundKnowledge of the relationships between patient‐reported and performance‐based walking measures in Parkinson's disease (PD) should inform clinical decision‐making. The Walk‐12G reliably captures perceived walking difficulties but has not been compared to performance‐based walking in laboratory or free‐living settings or across different groups.ObjectivesTo investigate the relationship between patient‐reported walking difficulties (Walk‐12G) and performance‐based walking in laboratory and free‐living c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…The independent variables in the present study were selected based on theoretical reasoning as well as on the results from previous cross-sectional studies 16,17 . The regression models in our study explained 61.7% and 67.6% of the variance in the Walk-12G scores, respectively.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent variables in the present study were selected based on theoretical reasoning as well as on the results from previous cross-sectional studies 16,17 . The regression models in our study explained 61.7% and 67.6% of the variance in the Walk-12G scores, respectively.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…One study found that two objective gait domains (i.e. pace and variability) were moderately associated with perceived walking di culties 16 . Another cross-sectional study, based on the same sample as the present study, identi ed FOG as the strongest contributing factor, followed by general self-e cacy, fatigue, PD duration, lower extremity function, orthostatic hypotension, bradykinesia and postural instability 17 .…”
mentioning
confidence: 99%
“…Some of those clinical studies aim at quantifying patient’s pathology [ 6 , 7 , 27 , 69 , 70 ], while others quantify the therapeutic effect on the patient’s condition [ 5 , 68 ]. Some clinical trials focus on healthy participants, some compare the patients included with healthy participants [ 39 , 42 , 71 , 72 ], while others dwell specifically upon cohorts with a medical condition. Perriot et al [ 7 ] intended to improve posture detection in COPD participants and Nguyen et al [ 63 ] focused on activity classification in patients with PD.…”
Section: Aims Of the Studiesmentioning
confidence: 99%
“…Finally, papers comparing the conditions and results in free-living conditions with those obtained in controlled environments [ 40 , 72 , 74 , 77 , 78 ] and papers dealing with the detection of ancillary parameters (such as wear-time [ 79 , 80 ], walking bouts [ 72 , 75 , 81 ], strides or steps [ 40 , 71 , 81 ], etc.) constitute the fifth and sixth distinct groups of respectively 10 studies and five studies.…”
Section: Aims Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation